Використання FPGA для реалізації штучної нейронної мережі - Луценко, А. В.; Чумак, В. С. (ХНУРЕ, 2022)
Advances in technology have greatly expanded the logical capabilities of FPGAs and, in turn, made them viable alternatives to large and complex implementations. Therefore, there is a prospect of implementing an artificial neural network on the FPGA. In the field of artificial intelligence and machine learning, an artificial neuron is a computing element that is a mathematical model of a biological neuron that is used as a basic element to build artificial neural networks.
Keywords: ПЛІС; FPGA; штучна нейронна мережа; нейрон